2003
DOI: 10.1108/09590550310497012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient retailer assortment: a consumer choice evaluation perspective

Abstract: This research shows that to reach their prime goal of building an efficient assortment, retailers need, beside increasing the outlet’s cost‐efficiency, to evaluate shoppers’ assortment perceptions so that what the store actually offers can be tailored to meet customers’ needs and expectations. Our findings reveal that consumers’ perceptions of the assortment range stems from the combination of few indicators, mainly the number of stock‐keeping units proposed and the availability of the favorite brands. Also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…Results indicated that shopping motives had an impact on consumers' attitudes towards retailers. Consistent support was found for the relationship between store image perception and product-specific variables (Amine & Cadenat, 2003;Porter & Claycomb, 1997;Collins-Dodd & Lindley, 2003) as well as store-specific variables (Joyce & Lambert, 1996;Mitchell & Kiral, 1998;Moore & Carpenter, 2006;Paulins & Geistfeld, 2003;Solgaard & Hansen, 2003;Shim & Kotsiopulos, 1992). Research on product-specific variables refers to brand image and label brand quality while store-specific variables refer to store type.…”
mentioning
confidence: 68%
“…Results indicated that shopping motives had an impact on consumers' attitudes towards retailers. Consistent support was found for the relationship between store image perception and product-specific variables (Amine & Cadenat, 2003;Porter & Claycomb, 1997;Collins-Dodd & Lindley, 2003) as well as store-specific variables (Joyce & Lambert, 1996;Mitchell & Kiral, 1998;Moore & Carpenter, 2006;Paulins & Geistfeld, 2003;Solgaard & Hansen, 2003;Shim & Kotsiopulos, 1992). Research on product-specific variables refers to brand image and label brand quality while store-specific variables refer to store type.…”
mentioning
confidence: 68%
“…CMKV Model variables are supported by research papers by Huddleston et al , 20 Descrochers and Nelson, 17 Dupre and Gruen, 25 Amine and Cadenat, 26 Basuroy et al , 27 and Aylott and Mitchell, 23 Huddleston et al 20 indicated a signifi cant impact of price, product assortment, customer service and product quality on customer satisfaction within conventional and specialty grocery stores. Descrochers and Nelson 17 highlighted behavior differences when a product is placed in different categories, presented in different brands and packaged in different designs and styles.…”
Section: Research Framework and Hypothesesmentioning
confidence: 87%
“…Chiefl y, measure contributions came from Descrochers and Nelson, 17 Dupre and Gruen, 25 Amine and Cadenat, 26 Busuroy et al , 27 and Aylott…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important is product assortment. Three of the most important factors consistently cited in the literature are location, price, and assortment (Hoch, Bradlow, & Wansink, 1999;Amine & Gadenat, 2003). In various studies, assortment ranks first or second in its influence on customer outcomes such as store choice, store loyalty, and satisfaction (Briesch, Chintagunta, & Fox, 2009;Sloot & Verhoef, 2008).…”
Section: Importance Of Assortmentmentioning
confidence: 99%